Korelasi Keterampilan Membaca Pemahaman Teks Eksplanasi Dengan Keterampilan Menulis Teks Eksplanasi - Sri Muliani; Erizal Gani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
There are three objectives of this research. First, describing the skills of reading comprehension of explanatory text. Second, describe the skills of writing explanatory text. Third, analyze the correlation of reading comprehension skills with explanatory text writing skills. This type of research is quantitative using the correlation method. The population of this study was class XI students of SMA Negeri 1 X Koto for the academic year 2022/2023 with a total of 167 students from five classes. The number of samples in this study was 15% of the population obtained by 25 students. The sampling technique in this study was simple random sampling. The instruments used in this study were objective tests to collect data on reading comprehension skills of explanatory texts and performance tests to measure writing skills of explanatory texts. There are three results of this study. First, students' reading comprehension skills of explanatory texts are at more than adequate qualifications, with an average score of 74.24. Second, the students' skills in writing explanatory texts are at more than adequate qualifications, with an average score of 75.22. Third, there is a correlation between the ability to read comprehension of explanatory texts and the skills of writing explanatory texts for class XI students of SMA Negeri 1 X Koto. Based on the results of the study, it was concluded that there was a correlation between the ability to read comprehension of explanatory texts and the skills of writing explanatory texts for class XI students of SMA Negeri 1 X Koto.